ESTABLISHMENT OF COTTON MONOPOLY POLICY OF AGRICULTURE IN UZBEKISTAN (1932-1936) - Ergashali Makhsudovich Erkaev (Journals Park Publishing, 2023)
In the article, the establishment of the policy of cotton monopoly in the agricultural sector of Uzbekistan during the Soviet period, its negative aspects in the period of 1932-1936, based on the information of primary sources and scientific literature, are highlighted.
Keywords: Cotton monoculture, Turkistan breeding station “Navrotsky”, “Kolkhozchi” (8517), “Uzbekistan” (36M2), MTS, Resolution “On the preparation of cotton processing and the collection of raw cotton”, irrigation, mechanization of agriculture, Northern Ferghana, Southern Ferghana, Tashkent channels.